Changing fate of large industrial investments during the Gomułka Period (1956–1970) - Kaliński, Janusz (Studia Historiae Oeconomicae, 2025)
The Gomułka period of fourteen years includes one of the investment cycles characteristic of the centrally managed economy in Poland. After an initial, short period of stabilization of outlays, in the years 1959–1969 they were significantly increased and clearly focused on the fuel, raw materials and chemical industry. The aim was to reduce the disproportions that had become apparent in the economy in the first half of the fifties, when heavy industry was particularly favored. Additional investments were focused on obtaining new production capacities in the scope of lignite and hard coal mining and the production of copper and sulfur, heat energy, liquid fuels and petrochemical products, non-ferrous metals and inorganic chemical products. As a result of the intensification of outlays, refinery and petrochemical plants in Płock, copper mines and metallurgy in Lower Silesia, chemical plants in Police and Puławy and coking coal mines in the Jastrzębie-Zdrój region gained a permanent position in the Polish economy. In the 1990s, the process of liquidation of the sulfur basin in the Tarnobrzeg region began, mainly under the influence of technological changes in the industry. At the beginning of the 21st century, the role of brown coal basins and the related energy industry in Lower Silesia and Wielkopolska decreased due to the gradual depletion of deposits.